A 12-week strength and conditioning intervention: an individualized case series approach for 3 amateur and 3 professional female golfers - Robinson, L.; Murray, A.; Coughlan, D.; Ehlert, A.; Heeney, C.; Turner, A.; Bishop, C. (The Journal of Strength and Conditioning Research, 2026)
This study used an individualized, case series approach to 12 weeks of strength and conditioning (S&C) training, for 3 high-level amateur and 3 professional female golfers. Each player took part in a 90-minute testing session both pre- and postintervention, and 2 structured S&C sessions per week for 12 weeks. Movement competency assessments were used to help guide exercise selection in each intervention and test measures included golf shot data, the isometric mid-thigh pull, isometric bench press, and countermovement jump, with a total of 12 metrics across the 4 assessment protocols. Analyses of individual performance changes were done by using the SD for each test metric, relative to preintervention scores. Collectively, for the 3 amateur players, 32 out of a possible 36 metrics showed changes > the baseline SD, while for the 3 professional players, 23 metrics elicited changes > the baseline SD. Of note, this collective difference was largely attributable to professional 1, who showed only 4 "true" improvements in test scores, out of a possible 12. This study has shown that taking an individualized approach to S&C training predominantly elicits meaningful changes in both golf shot data and physical performance—a concept that is essential to understand for an individual sport, such as golf.